GAME-BASED LEARNING IN DEVELOPING ORGANIZATIONAL AND MANAGEMENT COMPETENCIES - Kuzin, Oleksandr (The Modern Higher Education Review, 2025)
An overview was provided on why the adoption of educational gaming would benefit the organizational and managerial competence development of higher education students. Hence, this article paves the way for advancing the concept of simulations, role-plays, and business games as a new medium for imparting learning management skills that are both theoretical and practice-oriented. On the other side of the interdisciplinary approach, it states that there are cognitive, as well as social and emotional, dimensions to organizational managerial competence, which provides one with a wealth of strategic thinking, effective communication, evidence-informed decision-making, and teamwork. It harmonizes the newest advances and research about the application of game-based learning for future managers, educators, and social specialists. The article pays particular attention to game-based educational technologies as they bear a 'European' hallmark or feature when compared with other classical forms of education, in that they significantly impact motivation, development of critical thinking, self-reflection, and responsibility for common results. A classification of gaming methods related to management task integration is suggested: simulation models replicate professional activity in reality; role-play games develop communicative flexibility and leadership skills, while business games build competencies in the area of strategic planning and system views. The article proceeds with a description of the key strategic aspects pertaining to the effective use of Interactive Pedagogical Technologies (IPTs), namely, gradually increasing task difficulty, embedding games within subject content, utilizing reflective practices, and promoting teamwork. Through the consideration of these topics via virtualized digital simulation and the added value of content on a virtual platform, opportunities for distance and blended learning experiences are further expanded.